A guide to mental health for families and carers of people with intellectual disabilities - Holt, Geraldine, 1951- (Jessica Kingsley, 2004)
A practical and comprehensive introduction for carers to mental health problems, this accessible guide outlines a range of signs and symptoms of mental health problems that can affect people with intellectual disabilities. The guide explains why mental health problems develop, and advises on what can be done to help people with intellectual disabilities and carers themselves. With chapters on specific disabilities such as autism and epilepsy, the authors cover topics such as: treatment and interventions for mental health problems; getting the best services and understanding policy around menta.